2020
DOI: 10.1002/phar.2385
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hydromorphone versus Fentanyl‐based Sedation in Extracorporeal Membrane Oxygenation: A Propensity‐Matched Analysis

Abstract: INTRODUCTION Data comparing sedatives in patients receiving extracorporeal membrane oxygenation (ECMO) are sparse. However, it is known that the ECMO circuit alters the pharmacokinetic properties of medications via drug sequestration of lipophilic agents and increased volume of distribution. OBJECTIVES This study evaluated the difference in days alive without delirium or coma and the sedative requirements in patients receiving fentanyl versus hydromorphone in ECMO patients. METHODS This single-center retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
1
17
1
1
Order By: Relevance
“…The probable cause of relatively low recovery for the lipemic matrix was the selection of the extraction solvent and very high lipophilicity of the target compound. In the current study, 1-chlorobutyl and acetonitrile probably could not provide adequate lipid sequestration in the organic layer, as the dielectric constant of 1-chlorobutan is only 7.2 [51]. This resulted in visible, persisting milkiness of the plasma after the extraction.…”
Section: Discussionmentioning
confidence: 67%
“…The probable cause of relatively low recovery for the lipemic matrix was the selection of the extraction solvent and very high lipophilicity of the target compound. In the current study, 1-chlorobutyl and acetonitrile probably could not provide adequate lipid sequestration in the organic layer, as the dielectric constant of 1-chlorobutan is only 7.2 [51]. This resulted in visible, persisting milkiness of the plasma after the extraction.…”
Section: Discussionmentioning
confidence: 67%
“…This is consistent with Landolf and colleagues, who found higher delirium-free and coma-free days in the hydromorphone group, which was driven by coma-free days but not delirium-free days. 8 Although there were no differences in opioid or sedative (propofol and benzodiazepine) doses per ECMO day between groups, there was a significant decrease in propofol requirements on ECMO days three, four, and five for patients in the hydromorphone group. This finding requires more investigation as one may imply that hydromorphone patients may have reduced propofol requirements at the expense of greater benzodiazepine use.…”
Section: Discussionmentioning
confidence: 79%
“…To our knowledge, only two studies directly compare fentanyl to hydromorphone and their impact on patient-centered clinical outcomes. 8,9 Given the knowledge of pharmacokinetics, ex vivo data, and limited in vivo data, some institutions have established hydromorphone as the primary opioid used in ECMO patients. At our institution, fentanyl is most commonly utilized as the first-line opioid.…”
Section: Introductionmentioning
confidence: 99%
“…17,25 A retrospective observational study evaluating fentanyl-versus hydromorphone-based sedation in adult patients on ECMO support demonstrated lower narcotic requirements and more delirium-free and coma-free days in the hydromorphone cohort. 26 However, in a similar study, fentanyl-based sedation was shown to have numerically lower requirements of nonanalgesic sedatives and a statistically significant reduction in benzodiazepine requirements when compared to alfentanil, which is a less lipophilic fentanyl derivative. Therefore, the lipophilicity concerns do not appear to fully explain benefits seen with non-fentanyl-based sedation.…”
Section: Parenteral Opioidsmentioning
confidence: 94%